(untitled) (Indian Journal of Public Health Research & Development, 2020)
Objective: The objectives of this study were to evaluate the effectiveness of a participatory health promotion program for elderly with non-communicable diseases (NCDs) in municipalities, Thailand. Methodology: This experimental study was conducted among elderly who suffering from diabetes and/ or hypertension. The total samples of 84 of elderly with NCDs, of which 40 patients from 2 health centers were randomly allocated to the experimental group, whereas 44 from other 2 health centers were randomly allocated to a control group. Data were collected at baseline and 3 months after the implementation of a participatory health promotion program. The analysis of co-variance (ANCOVA) were used to determine effectiveness of the health promotion program. Results: The results indicated an effectiveness of the participatory health promotion program. After adjusting the baseline and controlling other covariates, the experimental group demonstrated improving of outcomes including reduced triglyceride(adjusted mean different = -32.15, 95% CI: -57.28 to -7.02)and increased HDL (adjusted mean different = 4.01, 95%CI: 1.11 to 6.89).